Peran Pendidikan Kewarganegaraan dalam Menguatkan Etika Digital dan Kesadaran Sosial Mahasiswa di Era Media Sosial - Supandri; Ulfah, Audya; Firmasnyah, Ilham; Nuraeni, Sri; Kius, Florentina Sindhi (Universitas Cokroaminoto Yogyakarta, 2025)
The social media era presents significant challenges to students' digital ethics and social awareness. The widespread spread of hoaxes, hate speech, and cyberbullying demonstrates a gap between technical skills and moral integrity in interacting in the digital space. This study aims to analyze the role of Civics Education (PKn), a compulsory general course in higher education, in shaping ethical and responsible Digital Citizenship. The method used is a qualitative descriptive literature study of scientific journals and related research results. The results show that PKn plays a crucial role through the integration of Pancasila values, democracy, and Human Rights (HAM) into the digital literacy curriculum. This strengthening not only improves students' ability to use technology safely and productively (digital literacy), but also contributes to the development of digital literacy. It also instills social responsibility and netiquette (internet ethics), which serve as the foundation for creating a constructive and civilized digital space. Research shows that Civics serves as an essential moral-ethical foundation, particularly through the integration of Pancasila and democratic values. However, its effectiveness is largely determined by innovative teaching methods (such as problem-based learning and case simulations) and the digital role models of educators. The main challenge faced is the consistent application of digital ethics by students outside the classroom context. A reconceptualization of Civics learning is needed to be more adaptive to the dynamics of social media. Learning must emphasize not only normative knowledge but also digital literacy skills and students' social responsibility as ethical netizens.